2011
DOI: 10.1017/s1368980011000929
|View full text |Cite
|
Sign up to set email alerts
|

The profile of the Greek ‘XXL’ family

Abstract: Objective: To identify Greek families in which all members were overweight or obese (XXL families) and to describe their profile with regard to their socioeconomic status and their eating behaviours and practices. Design: A prospective cohort study. Setting: The metropolitan area of Kavala. Subjects: We recruited children aged 11 and 12 years from twelve primary schools, and their parents, from volunteers. Auxologic measurements of the children included height and weight. A structured questionnaire pertaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Finally, recent studies report low adherence rates to the MD in Greek children and adolescents (Kontogianni et al, 2008) and high childhood obesity rates in Greek families of lower educational status and lower annual income (Christoforidis et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Finally, recent studies report low adherence rates to the MD in Greek children and adolescents (Kontogianni et al, 2008) and high childhood obesity rates in Greek families of lower educational status and lower annual income (Christoforidis et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…A key feature of the Mediterranean dietary pattern is the consumption of an adequate breakfast, which can be defined as the first meal of the day, taken before or at the start of daily activities with an energy content that meets 20-25 % of total daily energy needs (7)(8)(9) , and which includes dairy products, cereals, fruit and healthy fats. Among both adults and adolescents, the skipping of breakfast has been associated with smoking, infrequent exercise, low educational level, frequent alcohol use and high BMI (10)(11)(12)(13) . It has been reported that the failure to consume an adequate breakfast contributes to poor school performance and to dietary deficits that are rarely compensated for at other meals and may lead to a higher consumption of energy-dense snacks later in the day (14)(15)(16)(17)(18)(19)(20) .…”
mentioning
confidence: 99%